Hubungan Paparan Pestisida Pada Masa Kehamilan Dengan Kejadian Berat Badan Bayi Lahir Rendah (BBLR) di Kecamatan Ngablak Kabupaten Magelang - Setiyobudi, Bambang; Setiani, Onny; Wahyuningsih, Nur Endah (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2013)
Background : The use of pesticides in agriculture is a dilemma, because in addition to increasing agricultural output, also have an impact on human health. Maternal exposure to pesticides can cause reproductive disorders and birth of children with low birth weight (LBW). This study aims to association between the effect of pesticide exposure during pregnancy on the incidence of LBW in Ngablak Magelang regency. Methode: Research using observational designs with crossectional approach. The number of samples in this study were 76 mothers who had babies aged 0-12 months. Data were collected by interview using a questionnaire. In the study conducted from December 2011 to July 2012. Analyze of data with a frequency distribution, chi square and logistic regression. Result : The results showed that the incidence of LBW in theÂ NgablakÂ Sub District and as much as 22.4% in 2011. There were statistically significant effects of work related to pesticides (p = 0.0001), duration of exposure to pesticides (p = 0.0001), frequency of exposure to pesticides (p = 0.039) and use of PPE (p = 0.039) with the incidence of LBW. There is no significant effect of storage of pesticides (p = 0.634), pesticide handling equipment (p = 1.00), maternal age (p = 0.746), number of parity (p = 0.087) and maternal education (p = 0.60) with incidence of LBW. In multivariate work related to pesticides (p = 0.019) and duration of exposure to pesticides (p = 0.029) with the incidence of LBW in a large probability of 62,86%. Conclusion : The conclusion is that doing work related to pesticides and old pesticide exposure during pregnancy affect the LBW. When pregnant women should not exposed to pesticides or the use of PPE use in agriculture. Keywords: Pesticides Exposure Â , Pregnancy, Low Birth Weight (LBW)